Kinerja Rantai Pasok Tandan Buah Segar Kelapa Sawit dalam Meningkatkan Laba dan Mencapai Tujuan Perusahaan pada PT. Cahaya Cemerlang Lestari - Rumbiati, Rumbiati (Universitas muhammadiyah palembang, 2015)
Supply chain management of agro-industry places the management of crop and distribution becoming the key factor. The management system need to observe the cost and quality aspect. Supply chain management of palm oil need to consider the cost and quality as part of decision making. Both of the factors are important to analyze because the operational supply chain faces the action of qualityassurance to gain the economic scale. Supply chain performance depends on the decisions related to stock, production, and transportation. The delivery process of stem raw material in the supply chain at PT. CCL (Cahaya Cemerlang Lestari) was descriptively analyzed usingthe model of POA (Performance of Activity), including sevendimension of measurements. It is noticeable that the performance of fresh fruit stem (TBS) from the plantation is not satisfying where it is only two from 12 receivedmonths achieve the target of settled budget. However, theperformance of sortation and extraction activities is concluded satisfying where the achievement was more than the average of 95% in 2013. Following this, the performance of CPO production is concluded quite satisfying as it can be seen from the achievement of target is more than 80%. Additionally, the performance of CPO production quality is concluded very satisfying as it can be seen fromthe aspect of extraction rates, total losses/FFB, and the percentage of FFA, which can achieve the monthly target properly. Nevertheless, the performance of machine utility and production cost are concluded less satisfying because those items have not matched yet with the settled company target, where the number of machine utility do not reach 80% from January to July.